Pemberdayaan Masyarakat Dalam Pengembangan Museum Adityawarman Sebagai Objek Wisata Di Kota Padang - Adam Permana Yudha; Adrianus Tafoguna Hia; Alvin Alkhaira; Yulia Hanoselina; Rahmadhona Fitri Helmi (CV. ITTC INDONESIA, 2025)
This study aims to examine community empowerment strategies in the development of the Adityawarman Museum as a cultural-based tourist attraction in Padang City. The museum holds significant potential in preserving the historical and cultural values of the Minangkabau people while serving as an educational tourism site. However, local community involvement in its management and promotion remains limited. Using a literature review method, this research identifies challenges and opportunities in empowering the community and formulates relevant strategies such as engaging local communities in cultural events, implementing digital promotion, and improving supporting facilities. The findings suggest that effective community empowerment can enhance local participation, strengthen cultural identity, and support the sustainability of the museum as an inclusive and competitive tourism destination.